Treadmill exercise improves control over the HPA and HPG axes response to restraint stress in male rats - Kelestimur, H.; Bulmus, O.; Yardimci, A.; Tancan, E.; Serhatlioglu, I; Kacar, E.; Bulmus, Gulcu F. (Wiley, 2019)
[Abstract Not Available]